PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V.C SD NEGERI 62 PEKANBARU - Erma Erma; Jesi Alexander Alim; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve learning outcomes IPA of class IV Elementary School 003 Simpang Kota Medan in the academic year 2014/2015. The subjects were students class IV Elementary School 003 Simpang Kota Medan as many as 26 people. This study is a Class Action Research (Classroom Actions Research) which comprises two cycles. Based on the results of research and data analysis known that an increase in the percentage of teachers in the first cycle of activity amounted to 64.58% with sufficient qualifications, increased in the second cycle becomes 87.5% with excellent qualifications. The percentage of student activity in the first cycle of 54.17% with a less qualified, increased in the second cycle becomes 92,5% with excellent qualifications. In addition, the average value of daily test before applied science student cooperative learning model NHT is 56,35. In the first cycle UH 1 daily value increased to 65,96 students who have increased as much as 9,61 by the number of students who completed 14 students of 26 students. Thus, classical completeness obtained at UH 1 is 53,85%. At UH 2 increases in value an average of 23,27 into 89.23. All students completed the implementation of the UH 2, means being 100% classical completeness. Thus, it can be concluded that cooperative learning model NHT can improve student learning outcomes IPA class IV Elementary School 003 Simpang Kota Medan.Keywords : Cooperative Learning Model NHT, IPA Learning Outcomes